2013
DOI: 10.1371/journal.pone.0072778
|View full text |Cite
|
Sign up to set email alerts
|

How Does MBCT for Depression Work? Studying Cognitive and Affective Mediation Pathways

Abstract: Mindfulness based cognitive therapy (MBCT) is a non-pharmacological intervention to reduce current symptoms and to prevent recurrence of major depressive disorder. At present, it is not well understood which underlying mechanisms during MBCT are associated with its efficacy. The current study (n = 130) was designed to examine the roles of mindfulness skills, rumination, worry and affect, and the interplay between those factors, in the mechanisms of change in MBCT for residual depressive symptoms. An explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 47 publications
3
68
0
1
Order By: Relevance
“…Van Aalderen and colleagues [29] showed that the efficacy of MBCT, as compared with treatment as usual (TAU) in reducing levels of depression, was mediated by decreases in worry and rumination and increases in the mindfulness skill "accepting without judgement". Recently, Batink and coworkers [30] showed that changes in momentary positive and negative affect significantly mediated the efficacy of MBCT and the effect of changes in worry on depressive symptoms.…”
Section: Mindfulness-based Cognitive Therapymentioning
confidence: 99%
“…Van Aalderen and colleagues [29] showed that the efficacy of MBCT, as compared with treatment as usual (TAU) in reducing levels of depression, was mediated by decreases in worry and rumination and increases in the mindfulness skill "accepting without judgement". Recently, Batink and coworkers [30] showed that changes in momentary positive and negative affect significantly mediated the efficacy of MBCT and the effect of changes in worry on depressive symptoms.…”
Section: Mindfulness-based Cognitive Therapymentioning
confidence: 99%
“…Batink et al (43) demonstrated improvement in rumination scores in a group with ≥3 depressive episodes (MBCT + TAU) and in a group with ≥2 depressive episodes (TAU). In the study of Van Vugt et al (2) practicing MBCT decreased the scores of depression and anxiety, however, both groups (MCBT and Control) increased their tendency to sustain trains of positive words.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this theory, Geschwind and colleagues [ 66 ] found that MBCT compared to a waitlist control increased momentary positive emotions and reward from pleasant daily life activities for people with a history of MDD and current residual depressive symptoms. Batink and colleagues [ 64 ] found that changes in positive affect mediated 61 % of the effect of MBCT on residual depressive symptoms. And Garland and colleagues [ 65 ] found that MBCT enhanced momentary positive cognition, and appeared to strengthen the relationship between current positive affect and positive cognition the next day.…”
Section: Mechanism Of Changementioning
confidence: 99%
“…Another RCT with patients with three or more previous depressive episodes, with and without a current depressive episode, found that effect on depressive symp-toms were mediated by a decrease in worry and rumination, and an increase in the mindfulness skill "accept without judgment" [ 32 ]. Batink and colleagues [ 64 ] found that the effects of MBCT on residual symptoms of depression were mediated by changes in mindfulness skills and worry, but did not fi nd rumination to be a mediator.…”
Section: Mechanism Of Changementioning
confidence: 99%